Cardiac arrhythmias in cancer patients. Part II. QTc prolongation, ventricular tachycardia, electrical storm and sudden death - V. Y. Tseluyko; N. E. Mishchuk (Medicine of Ukraine, 2026)
The lecture is devoted to electrical storm (ES) – a state of electrical instability of the heart with the occurrence of sustained ventricular tachycardias, at least three in 24 hours, which is accompanied by high mortality and requires urgent multidisciplinary treatment. ES is often found in patients with an implanted cardioverter-defibrillator. Most cases of ES occur on the background of structural heart pathology and manifest with monomorphic ventricular tachycardia. Polymorphic ventricular tachycardia and ventricular fibrillation are more likely in conditions of acute ischemia and primary channelopathies. In the treatment of ES, the search and correction of triggers, ICD reprogramming, drug therapy with the use of beta-blockers, sedatives and antiarrhythmic drugs, autonomic modulation, catheter ablation and hemodynamic support are important. The choice of initial therapy and its subsequent stepwise escalation are based on the risk stratification of ES. The theoretical material of the lecture is illustrated by the authors' own clinical observation. The lecture will be useful for doctors – cardiologists, anesthesiologists, emergency medicine and family doctors.